INFLUENCE OF PERSONAL ATTRIBUTES ON DIGITAL ENTREPRENEURIAL INTENTION: THE ADDED IMPACT OF ENTREPRENEURIAL PASSION AND CREATIVITY - Monira , Nurjahan Akter; Sultana , Ireen; Krings , Werner; Tazin , Fariha; Sharmen , Sayma (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
Digital entrepreneurship is gaining global relevance as digital technologies transform the way ventures are conceived and launched. However, the individual-level traits influencing digital entrepreneurial intention (DEI) remain under-examined. This study extends prior frameworks by integrating two novel predictors, entrepreneurial passion and creativity, alongside five established traits: empathy, prior Experience, locus of control, self-efficacy, and risk-taking Tendency. Using a structured questionnaire, data were collected from 589 Bangladeshi university students, a population well-positioned as future digital entrepreneurs. Multiple regression analysis revealed that all seven personal attributes significantly and positively influence DEI (p < 0.05). The extended model accounted for 59.4% of the variance in DEI (Adjusted R² = 0.594, F(7, 581) = 122.4, p < 0.001). Quantitatively, risk-taking Tendency (β = 0.301, p < 0.001) and entrepreneurial passion (β = 0.244, p < 0.001) emerged as the strongest predictors. Creativity (β = 0.127, p = 0.002), locus of control (β = 0.119, p = 0.001), and self-efficacy (β = 0.102, p = 0.004) followed in magnitude. Empathy (β = 0.079, p = 0.024) and prior Experience (β = 0.058, p = 0.047) also showed statistically significant but comparatively smaller effects. These results highlight that both affective (passion, empathy) and cognitive (creativity, self-efficacy, locus of control) traits play a pivotal role in fostering digital entrepreneurship. The findings underscore the importance of cultivating emotional motivation and innovative capacity in digital entrepreneurship education. Overall, this study presents a robust empirical model that explains DEI, offering practical implications for entrepreneurship educators and policymakers in developing contexts.JEL Classification Codes: L26, M13, O33.